Anxiety and Depressive Symptomatology among Iranian Patients Hospitalized for COVID-19 in January 2020 - Victoria Omranifard; Gholamreza Ghassemi Toudeshkchuie; Niloofar Nikfarjam; Ali Gharavinia (Zanjan University of Medical Sciences and Health Services, 2023)
Background: Widespread outbreaks of Coronavirus disease among Iranian people are not only associated with physical illness but also with psychological symptoms which need special attention. Objectives: This study was an endeavor to examine the relationship between comorbidity and death anxiety with Anxiety and Depressive Symptomatology among those survived after the COVID-19 pandemic in Iran. Methods: This was a cross-sectional study in which the probands o survivors of COVID-19 participated. By means of convenient smpling method and adhering to selection criteria we chose 300 patients admitted for COVID-19 in a university affiliated hospital in Isfahan-Iran during the January 2020. We collected the data pertaining to their illness history, including information about their comorbidity and demographic background by means of an interview schedule with closed-ended questions. We used the Persian version of Templer's Death Anxiety Scale (TDAS) and Hospital Anxiety and Depression Scale (HADS). Data were computer analyzed using SPSS-19 and running Hierarchical Log-linear analysis symptomatology in a saturated model. Results: Majority of the participants were female (64%) with the mean (SD) age of 44.8 (12.8) years. Positive comorbidity was accompanied by a higher chance of exhibiting depressive symptoms (OR=34.67, df =1, P=0.000). High death anxiety was accompanied by higher chances of anxiety-depressive symptoms (OR=90.13, df =1, P=0.00). Conclusion: These observations reinforce the hypothesis proposed on the basis of Hill's (1958) ABC-X model and provided impetus to idea that how absence of comorbidity and positive perception of illness condition protect individuals from psychological hazards of COVID-19.